Artikel Ilmiah Analisis Tingkat Keterampilan Gerak Dasar fundamental Movements Skills (FMS) usia 7-8 tahun di SDN Buduran Kabupaten Sidoarjo: Analisis Tingkat Keterampilan Gerak Dasar fundamental Movements Skills (FMS) usia 7-8 tahun di SDN Buduran Kabupaten Sidoarjo - Muhammad Zaidan Barki Muslim; Achmad Widodo; Noortje Anita Kumaat; Irmantara Subagio (Jurnal Porkes, 2026)
Fundamental Movement Skills (FMS) are a crucial foundation for the motor development of elementary school-aged children. However, systematic evaluations of students’ FMS abilities at the local level remain limited, making it difficult for teachers to design targeted instruction. This study aims to analyze the level of fundamental movement skills among lower-grade students aged 7–8 years at SDN Buduran Sidoarjo across the three main FMS domains: locomotor, manipulative, and stability. The study employed a descriptive quantitative approach with a sample of 40 students selected using total sampling. The instrument used was a performance-based checklist adapted from the Western Australia FMS Manual (2013) and had undergone an inter-rater calibration process. The results showed that, overall, students’ FMS abilities fell into the “moderately developed” category, with the majority of students concentrated in the “Moderate” (45%) and “Poor” (35%) categories. Analysis by domain showed that locomotor skills had the highest mean (M = 2.33), while manipulative skills showed the lowest performance (M = 2.26) with the greatest variation in ability. The conclusion of this study is that manipulative skills are the students’ primary weakness and require a more structured, sustained, and child-centered physical education intervention based on children’s motor development needs.